Best practices in road transport: An exploratory study - Mar Fernández Vázquez-Noguerol; Iván González-Boubeta; Pablo Domínguez-Caama\~no; José Carlos Prado-Prado (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: Road transport aspects are becoming increasingly important due to their high impact on economic, environmental and social sustainability. Considering the triple bottom line approach, best practices play a fundamental role within organisations. The purpose of this paper is to analyse several sustainable initiatives in road transport adopted by companies. Design/methodology/approach: The findings were developed and evaluated based on empirical data captured through a survey of 98 professionals involved in logistics and transport activities. Additionally, key literature on transport initiatives was reviewed to supplement the framework for the implementation of best practices in road transport. Findings: The exploratory study shows the importance of each best practice and determines the level of implementation of each initiative, comparing the results among different dealers (retailers, wholesalers, carriers and manufacturers), type of transport fleet and companies' revenues. Research limitations/implications: The sample of 98 companies was based on simple search filters and the group is not wholly representative of all sectors. Respondents were mainly managers from Spain involved in logistics and transport activities. Surveyed companies included manufacturing, retailers, wholesalers and third-party logistics providers. Practical implications: The most common best practices in road transport are identified, including initiatives related to: efficiency, reusability, safety, optimization, emissions, waste and recycling. Initiatives that influence road transport are ranked by their degree of implementation in the companies analysed. Social implications: Implementation of some of these best practices may help lessen negative impacts of road transport on society and the environment. Originality/value: The study results indicate which practices are most frequently used and their level of implementation depending on companies' roles in the supply chain, revenues and types of transport fleet. By implementing the proposed best practices, companies will adopt sustainable behaviors to improve their transport performance.
Keywords: 650; sustainability; road transport; best practices; supply chain; logistics